The Effect of Service Quality and Trust on Patient Satisfaction - Al Maududi, Abul A'la; Jaksa, Suherman (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2024)
The purpose of this study was to determine and analyze: (1) Service quality; (2) Trust; (3) Patient Satisfaction and (4) The effect of service quality performance and trust on patient satisfaction in the eye disease clinic of Santosa Hospital Bandung Central. The research method used in this research is descriptive survey and explanatory survey, the unit of analysis in this study is the Eye Disease Poly of Santosa Hospital Bandung Central with a sample of 50 people. The type of investigation is causality, and the time horizon in this study is cross-sectional.Based on the results of the study, it was found that the performance of service quality according to the Eye Disease Poly of Santosa Hospital Bandung Central was generally not good; Trust according to the Eye Disease Poly of Sentosa Hospital Bandung Central is generally good and Patient Satisfaction of the Eye Disease Poly of Sentosa Hospital Bandung Central is currently considered good. Service quality and trust affect patient satisfaction in the eye disease clinic of Santosa Hospital Bandung Central. Because trust affects patient satisfaction dominantly, the Eye Disease Poly of Santosa Hospital Bandung Central must maintain conditions so that patient satisfaction at the Eye Disease Poly of Santosa Hopitaal Hospital Bandung Central remains consistent, so that patient satisfaction is formed strongly and rooted.